2020
DOI: 10.1049/iet-map.2019.0365
|View full text |Cite
|
Sign up to set email alerts
|

Broadband planar slot antenna using a simple single‐layer FSS stopband

Abstract: In this study, the authors propose a simple structure of a new broadband planar slot antenna using a wide single‐layer frequency selective surface (FSS) stopband. The proposed design is realised in two stages. First, the performances of the FSS unit cells are investigated using the finite element method of high‐frequency structure simulator. Besides, the FSS structure considered as a stop‐band filter in the bandwidth false(3−7thinmathspaceGHzfalse), is also validated by computer simulation technology microwave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…s H is the distance between the antenna and the FSS reflector, c is the velocity of the light, and F t must be a multiple of 2π to obtain a coherence phase [34,35]. It is expressed as follows:…”
Section: Performance Analysis With Different Gap Values Between Anten...mentioning
confidence: 99%
“…s H is the distance between the antenna and the FSS reflector, c is the velocity of the light, and F t must be a multiple of 2π to obtain a coherence phase [34,35]. It is expressed as follows:…”
Section: Performance Analysis With Different Gap Values Between Anten...mentioning
confidence: 99%
“…The FSS reflecting layer is composed of a 7 × 7 FSS array, and the proposed FSS‐backed UWB antenna is illustrated in Figure 14. When using a single FSS layer reflector concept, with our UWB antenna placed above it at a distance D z , the reflected wave from the FSS layer is added to the direct radiation from the antenna itself, leading to a constructive interference, when these two waves are in phase, at the reference plane T, and the total phase ϕ T is described as follow 29 : ϕTgoodbreak=ϕSgoodbreak+ϕR where ϕSgoodbreak=22italicπfcDz …”
Section: Fss‐backed Uwb Antennamentioning
confidence: 99%
“…8(c) and 8(d). It was found that the gain of the antenna in the existence of the FSS reflector would be maximum when two components-the round-trip free space propagation phase delay between the antenna and the FSS reflector in the R-plane (𝜑 ) and the reflected back-radiated waves from the antenna toward the FSS (𝜑 )-were added in the phase, which triggered a rise in the constructive interference [19]. The evaluation of the phase at the reference T-plane is depicted by the following equation:…”
Section: Application Of Fss On Antenna Performancementioning
confidence: 99%
“…At this time, a maximum gain of around 5 dBi had been obtained, which improved the impedance bandwidth by only 2.37% at 2.45 GHz and 2% at 5.8 GHz. Other common applications of FSS were illustrated in [16][17][18][19][20][21]. Generally speaking, those reports utilized the classical design methods and proposed fundamental structures, which resulted in certain disadvantages such as low gain enhancement, low impedance bandwidth, high profile, and difficult manufacture.…”
Section: Introductionmentioning
confidence: 99%